2015
DOI: 10.1007/s11663-014-0264-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Control for Al2O3 Inclusion Without Ca Treatment in High-Aluminum Steel

Abstract: Nozzle blockage is a major problem during continuous casting of Al-containing steel. Herein, we analyzed the thermodynamic equilibrium behavior between aluminum and oxygen in steel at 1873 K (1600°C) and demonstrated that, the dissolved [O] initially decreases with increasing the dissolved [Al] until approximately 0.1 wt pct [Al], and after that, the dissolved [O] increases with dissolved [Al]. Thus, for high-aluminum steel with 1.0 wt pct dissolved [Al], the precipitation of Al 2 O 3 inclusion can be avoided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…MgO · Al 2 O 3 and CaO–Al 2 O 3 phases are known to be thermodynamically more stable than the Al 2 O 3 phase in commercial steels with reduction refining . In this study, the MgO · Al 2 O 3 phase was detected in inclusions similarly to those found in the previous work .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…MgO · Al 2 O 3 and CaO–Al 2 O 3 phases are known to be thermodynamically more stable than the Al 2 O 3 phase in commercial steels with reduction refining . In this study, the MgO · Al 2 O 3 phase was detected in inclusions similarly to those found in the previous work .…”
Section: Discussionsupporting
confidence: 84%
“…Modifying Al 2 O 3 or MgO · Al 2 O 3 into liquid CaO–Al 2 O 3 inclusions can prevent nozzle cloggings . Therefore, the mechanism of the inclusion evolution from Al 2 O 3 or MgO · Al 2 O 3 phase into the liquid CaO–Al 2 O 3 phase has been deeply studied in both laboratory and plant scale trials …”
Section: Introductionmentioning
confidence: 99%
“…A low melting point of the slag provides a good condition for a fast metal-slag separation. In addition, the dissolution time of Al 2 O 3 inclusion in the high basicity slag is much shorter than the separation time of Al 2 O 3 at the slag-metal interface (< 5 s) [25]. At the same time, the dissolution rate of Al Table 4 shows the chemical composition of alloys.…”
Section: Characteristics Of Slagsmentioning
confidence: 99%
“…The reaction produces new oxides that have a lower interfacial energy with the melt and also possibly form clathrate compound with the residual aluminum oxide inclusions 51, 52 .…”
Section: Design Of Fluxing Agentmentioning
confidence: 99%
“…Thus, a large negative Δ G c v signals an easier reaction. The formation of different products such as MgO or clathrates in the melt could be determined by the equilibrium constant of the actual molten salt system 52 . This is consistent with West’s view 55 .…”
Section: Design Of Fluxing Agentmentioning
confidence: 99%